A Review of Bancassurance: Exploring the advantages and disadvantages of bancassurance (Journal of Advances and Scholarly Researches in Allied Education, 2023)
In a bancassurance partnership, a bank and insurer work together to market and sell insuranceto the bank's customer base. Each company stands to gain from this potential cooperation. When banksprovide insurance to their customers, both the bank and the insurance company benefit from thetransaction. In this article, we will examine the benefits and drawbacks of bancassurance.